ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT. INDAL ALUMUNIUM INDUSTRI, TBK - Susilawati, Yuyun; Rimawan, M. (Jurnal Manajemen, 2023)
This study aims to identify and analyze the financial statements to assess the financial performance of PT. Indal Aluminum Industry, Tbk. This research is a descriptive type using a research instrument in the form of a list of tables. The population used in this study is the entire financial statements of PT. Indal Aluminum Industri, Tbk since being listed on the IDX from 1994 to 2022, namely for 28 years. The sample in this study is the financial statements of PT. Indal Aluminum Industri, Tbk for 10 years, from 2013 to 2022. The sampling technique used in this study was a purposive sampling technique for data collection using documentation and literature study. The data analysis technique uses percomponent ratio analysis and One Sample t-tes). The results showed that the liquidity ratio as measured by the Current Ratio (CR) was in a bad predicate or <200%, the solvency ratio as measured by the Debt To Asset Ratio (DAR) was in a bad predicate or > 35%, the profitability ratio as measured with Return On Equity (ROE) being in a bad predicate or <40%, the activity ratio as measured by Fixed Assets Turnover (FATO) is in a bad predicate or <5 times.